PERENCANAAN JALAN SURYAKENCANA – SILIWANGI SEBAGAI RUANG INTERPRETASI BUDAYA DI KAWASAN PECINANKOTA BOGOR - Moh. Sanjiva Refi Hasibuan; Ray March Syahadat; Nuraini Nuraini; Nurhayati H.S. Arifin (BUANA SAINS, 2016)
Each year, Chinatown of Bogor Municipality as heritage city whichis located on Suryakencana - Siliwangi Road usually hold Cap Go Meh celebration. By 2013, this tradition was held again by the name of Bogor Street Festival. The rapid development and an increasing number of vehicles became a problem in this activity. Based on the description of the problem, it is necessary to plan the Suryakencana-Siliwangi Road as a space of cultural interpretation in the Chinatown area of Bogor, in order to obtain an act of preservation and development of cultural activities in order to avoid loss of quality in the cultural activities. The results of this study are obtained by an appropriate planning concepts for the Chinatown area of Bogor especially Suryakencana – Siliwangi’sstreetscape as cultural path. The concepts are improving the function of space planning and optimizing the use of the existing space to support the Cap Go Meh celebration in order to provide the knowledge, experience, comfort and satisfaction for the participants and visitors. This concept was then developed into the concept of circulation and concept of space then overlaid to produce an appropriate block plan